FIT-Binding Proteins and Their Functions in the Regulation of Fe Homeostasis - Wu, Huilan; Ling, Hong-Qing (Frontiers in Plant Science, 2019)
Iron, as an essential micronutrient, is required by all living organisms. In plants, the deficiency and excess of iron will impair their growth and development. For maintaining a proper intracellular iron concentration, plants evolved different regulation mechanisms to tightly control iron uptake, translocation and storage. FIT, a bHLH transcription factor, is the master regulator of the iron deficiency responses and homeostasis in Arabidopsis. It interacts with different proteins, functioning in controlling the expression of various genes involved in iron uptake and homeostasis. In this review, we summarize the recent progress in the studies of FIT and FIT-binding proteins, and give an overview of FIT-regulated network in iron deficiency response and homeostasis.